Educational Financial Management in Providing School Needs - Baidowi, Ach.; Chasan Ma’ruf; Riski Aulia Rahmah; Rosa, Rosa; Salma, Salma; Tsania Ruhama Nadzyra; Wulan Mawalita (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2024)
The research aims to explain and describe financial management in education to meet the needs of Private Elementary School 2 Muhammadiyah Kotabaru. The study employs a qualitative method through a case study approach. Data collection techniques include interviews with the school principal, teachers, and administrative staff. Data processing involves reduction, data presentation, and drawing conclusions. Data validity is ensured through credibility and confirmability. The research findings include: (1) financial planning by creating a school budget work plan at the beginning of the academic year, (2) financial organization by categorizing fund usage to meet process standards, management, and educational needs, (3) fund utilization for office supplies, learning media, school cleanliness, teacher and educational staff honorariums, and others, (4) financial control by comparing financial plans with expenditures. In conclusion, financial management has been implemented effectively, as evidenced by the appropriate utilization of school funds in accordance with the school budget plan, up to periodic and continuous financial control.